Analisis Kesalahan Berbahasa pada Teks Laporan Penelitian Berdasarkan Pedoman Umum Ejaan Bahasa Indonesia (PUEBI) - Khairunissa Khairunissa; Grace Shintia Ori Simamora; Elsa Yolanda Simanjuntak; Domma Wati Klara Sitinjak; Valentina Angel Cristiani Sinaga (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2026)
This study analyzes language errors in research report texts based on the General Guidelines for Indonesian Spelling (PUEBI). The three research report texts analyzed come from scientific journals published in 2024, namely: (1) "Prinsip Pembelajaran Kurikulum Merdeka (Tinjauan Holistik Paradigma Ki Hajar Dewantara sebagai Pendekatan)," published in NUSRA: Jurnal Penelitian dan Ilmu Pendidikan; (2) "Implementasi Penggunaan Teknologi Digital sebagai Media Pembelajaran Pada Pendidikan Inklusi di Indonesia," published in Jurnal Educatio; and (3) "Analisis Permasalahan Kualitas Pendidikan Indonesia," published in Cendikia: Jurnal Pendidikan dan Pengajaran. This study employs a descriptive qualitative method with documentation and note-taking as data collection techniques. The data were analyzed using PUEBI as the reference standard to identify types of language errors, including errors in capital letter usage, punctuation, word writing, and foreign or loanword writing. These errors were found in various parts of the texts, including titles, abstracts, article bodies, and reference lists, indicating that inconsistent application of spelling rules remains a common issue in Indonesian academic writing. The results of this study are expected to make a meaningful contribution to improving the quality of scientific writing in Indonesian academic journals, while also serving as a reference for authors, editors, and journal managers in paying greater, more consistent, and more responsible attention to the linguistic aspects of scholarly work, in order to advance national scientific literacy.